2022
DOI: 10.3390/ijerph191811342
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality and Cancer Prevalence Trends across the Sub-Saharan African Regions during 2005–2020

Abstract: Poor air quality and environmental pollution remain some of the main etiological factors leading to cancers and cancer-related deaths worldwide. As a result of human activities, deleterious airborne chemicals can be dispersed not only in the environment but also released in occupational environments and industrial areas. Air pollutants and cancer links are now established through various oxidative stress-related mechanisms and related DNA damages. Generally, ambient and indoor air pollutants have been understu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that the incidence of cancer and the level of air pollutants have increased significantly, including but not limited to lung cancer, breast cancer, etc. Adhikari A. and others found that in some sub-Saharan countries, the incidence of cancer and the level of air pollutants have increased significantly in the past 15 years ( 13 ). Cooking and indoor incineration have been identified as significant risk factors for lung cancer, especially among women ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the incidence of cancer and the level of air pollutants have increased significantly, including but not limited to lung cancer, breast cancer, etc. Adhikari A. and others found that in some sub-Saharan countries, the incidence of cancer and the level of air pollutants have increased significantly in the past 15 years ( 13 ). Cooking and indoor incineration have been identified as significant risk factors for lung cancer, especially among women ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is the leading cause of mortality globally, with approximately 10 million deaths recorded in 2020 and an estimated 28.4 million new cases expected by 2040 [149]. The lack of physical activity, obesity, tobacco use, alcohol use [150,151], exposure to ultraviolet radiation [152], and exposure to an environment polluted with nitrogen dioxide [153], sulfur dioxide, carbon monoxide [154,155], suspended particles [156], and persistent organic pollutants (POP) such as polycyclic aromatic hydrocarbons [157,158], all contribute to the development of various types of cancer, the most prevalent of which are breast cancer [159], colorectal cancer [36,160], lung cancer [154], prostate cancer, and gastric cancer [161].…”
Section: Anticancer Propertiesmentioning
confidence: 99%